COMPARATIVE MORPHOLOGY OF THE NERVOUS SYSTEM OF THE LIVER OF MAMMALS WITH DIFFERENT TYPES OF FOOD. - Dilfuza S. Shodiyarova (TADQIQOTLAR, 2025)
ABSTRACT This article analyzes the scientific literature on the study of the nervous system of the liver of mammals with different types of food and describes the unexplored aspects of this problem. 10 rabbit livers representing herbivore mammals and 10 dog livers representing carnivore mammals were taken for study. The results of the research revealed that the nervous system of the liver of mammals has specific morphofunctional properties depending on the type of food.